Model Biaya Produksi Biodiesel Berbasis Minyak Sawit - Sembiring, Meilita Tryana; Sukardi, Sukardi; Suryani, Ani; Romli, Muhammad (Institution for Industrial Research and Standardization of Industry - Padang, 2015)
Biodiesel is a renewable energy source in Indonesia of which the use is regulated by the government in the form of mandatory policy of biodiesel and diesel fuel blending. The production of biodiesel in Indonesia is not developed (the need is 3.4 million kiloliters but the total national production is only 1,703 kiloliters). It is because the selling price (referring to Mean of Platts Singapore) is always lower than the production cost. Biodiesel production is influenced by raw materials and process technology, so it needs to be conducted biodiesel production modeling as a basis in determining the supporting policies of biodiesel selling price. The purpose of this study is to identify the raw materials, process technology, and modeling the production cost structure of palm oil-based biodiesel. Identification of raw materials was conducted by literature study and field survey to biodiesel producers. Identification of process technology was conducted by field survey and mass balance calculation using Grand Inizio technology to get the number of yield of each raw material. Then, production cost study was based on the specifications of raw materials and process technology with heuristic approach. Types and specifications of palm oil widely used by Indonesian producers are Crude Palm Oil (CPO) FFA<5%, Refined Palm Oil (RPO) FFA<5%, Refined Oil FFA<1%, Palm Fatty Acid Distillated (PFAD) FFA 90%. The technology process used was transesterification for FFA level <1% and esterification-transesterification for FFA level <5%. The resulting yield for 1000 kg of raw material is 1051.75 kg CPO, 975.94 kg RPO and PFAD, 973.81 kg Refined Oil with Grand Inizio technology approach. The production cost model represents the total production cost influenced by the costs of Inside Battery Limit, Outside Battery Limit, general cost and glycerol value-added.ABSTRAKBiodiesel adalah sumber energi terbarukan di Indonesia yang diatur penggunaannya oleh pemerintah dalam bentuk kebijakan mandatori pencampuran biodiesel dengan solar (biosolar). Produksi biodiesel di Indonesia tidak berkembang (kebutuhan 3.4 juta kiloliter namun total produksi nasional hanya 1.703 kiloliter). Hal tersebut disebabkan harga jual (mengacu Mean of Platts Singapore) yang selalu lebih rendah dibandingkan biaya pokok produksi. Produksi biodiesel dipengaruhi oleh bahan baku dan teknologi proses, sehingga perlu dilakukan pemodelan produksi biodiesel sebagai landasan dalam menentukan kebijakan pendukung harga jual biodiesel. Tujuan penelitian ini adalah mengidentifikasi bahan baku, teknologi proses, dan memodelkan struktur biaya produksi biodiesel berbasis minyak sawit. Identifikasi bahan baku dilakukan dengan studi literatur dan survei lapangan ke produsen biodiesel. Identifikasi teknologi proses dilakukan dengan survei lapangan dan perhitungan neraca massa dengan teknologi Grand Inizio untuk mendapatkan jumlah rendemen dari masing-masing bahan baku. Selanjutnya kajian biaya produksi dilakukan berdasarkan spesifikasi bahan baku dan teknologi proses dengan pendekatan heuristik. Jenis dan spesifikasi minyak sawit yang banyak digunakan produsen di Indonesia adalah Crude Palm Oil (CPO) ALB<5%, Refined Palm Oil (RPO) ALB<5%, Refined Oil ALB<1%, Palm Fatty Acid Distillated (PFAD) ALB 90%. Teknologi proses yang digunakan adalah transesterifikasi untuk kadar ALB<1% dan esterifikasi-transesterifikasi untuk kadar ALB<5%. Rendemen yang dihasilkan untuk 1000 kg bahan baku adalah CPO 1051.75 kg, RPO dan PFAD 975.94 kg, Refined Oil 973.81 kg dengan pendekatan teknologi Grand Inizio. Model biaya produksi merepresentasikan total biaya produksi yang dipengaruhi oleh biaya Inside Battery Limit, Outside Battery Limit, biaya umum dan nilai tambah gliserol.